Inferior oblique muscle recession with and without superior oblique tendon tuck for treatment of unilateral congenital superior oblique palsy - Kaeser, Pierre-François; Klainguti, Georges; Kolling, Gerold (Journal of the American Association for Pediatric Ophthalmology and Strabismus, 2012)
Purpose: To compare the surgical results in patients with congenital superior oblique palsy treated with inferior oblique recession (IOR) versus those treated additionally with superior oblique tendon tuck (IOR+SOT). Methods: A consecutive, nonrandomized series of patients with congenital superior oblique palsy with vertical deviations in adduction between 10° and 20° were retrospectively reviewed. In the first series, patients were treated with IOR; in the second series, patients were treated with IOR+SOT. We examined the effects of surgery on binocular alignment and on the field of binocular single vision. Results: Each group consisted of 20 patients. Preoperative ocular deviations were similar in both groups. Postoperative residual vertical deviations were not different in the primary position or in downgaze; however, significantly better alignment was achieved in the IOR+SOT group in adduction and downgaze in adduction. Consecutive Brown pattern occurred in 18 of 20 patients who underwent IOR+SOT versus 5 of 20 who underwent IOR. Residual torsion was not statistically different. The field of binocular single vision improved to 92% (range, 28%-100%) after IOR and to 96% (range, 64%-100%) after IOR+SOT (P = 0.20). Conclusions: IOR alone is a suitable procedure for most congenital superior oblique palsies with a moderate-to-large vertical deviation in adduction, resulting in a lower incidence of consecutive Brown pattern than with IOR+SOT.